2012
DOI: 10.3174/ajnr.a3328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patient Sex on White Matter Alterations in Unilateral Medial Temporal Lobe Epilepsy with Hippocampal Sclerosis Assessed by Diffusion Tensor Imaging

Abstract: BACKGROUND AND PURPOSE: Studies shows ictal behavior and symptoms are affected by patient sex in temporal lobe epilepsy. The purpose of our study was to determine whether alterations in the WM as assessed by DTI display different patterns in male and female patients with unilateral HS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…We found more bilateral changes in right TLE than left TLE, the converse of previous studies (Ahmadi et al, 2009; Kemmotsu et al, 2011). However as diffusion changes in right TLE were found to be more widespread and bilateral in females than males (Oguz et al, 2013), the gender imbalance in our right TLE group, which was 79% female, could explain this difference. The presence of baseline changes highlights the importance of including controls and preoperative imaging, as a previous study comparing postoperative imaging in patients to healthy controls and demonstrating widespread reductions in FA within ipsilateral tracts was unable to conclude whether these changes were pre-existing as a result of the disease or developed following surgery (Schoene-Bake et al, 2009).…”
Section: Discussionmentioning
confidence: 51%
“…We found more bilateral changes in right TLE than left TLE, the converse of previous studies (Ahmadi et al, 2009; Kemmotsu et al, 2011). However as diffusion changes in right TLE were found to be more widespread and bilateral in females than males (Oguz et al, 2013), the gender imbalance in our right TLE group, which was 79% female, could explain this difference. The presence of baseline changes highlights the importance of including controls and preoperative imaging, as a previous study comparing postoperative imaging in patients to healthy controls and demonstrating widespread reductions in FA within ipsilateral tracts was unable to conclude whether these changes were pre-existing as a result of the disease or developed following surgery (Schoene-Bake et al, 2009).…”
Section: Discussionmentioning
confidence: 51%
“…In addition, memory performance of chronic smokers is less than non-smokers (p<0.05) and our study shows statistically significant low correlation about memory performance with FA values in nonsmoking group. Although many studies have been performed regarding hippocampal DTI measurements in Alzheimer disease, vascular dementia, epilepsy, age-related changes and cerebral small vessel disease, to the best of our knowledge, our study is the first report that showed hippocampal DTI measurements with memory performance in chronic smokers [12][13][14][15][16][17]. We hypothesized that chronic smoking would adversely affect the hippocampal structural integrity and memory performance.…”
Section: Discussionmentioning
confidence: 81%
“…In this regard, an individual inspection of the FA results in the LATL group did not show a difference based on MTS. Fourth, gender distribution was different between our groups, raising a concern about gender related white matter changes [74]. However, the sample size available was too small to allow for a proper control of this variable.…”
Section: Discussionmentioning
confidence: 87%